Shrinkage and Mechanical Properties of Fibre-Reinforced Blast Furnace Slag-Steel Slag-Based Geopolymer - Shengtang Xu; Chaofan Wu; Jinchao Yue; Zikai Xu (Advances in Civil Engineering)
Geopolymer materials have several obvious advantages such as energy conservation, emission reduction, and waste reuse, so they can become substitutes for cement materials. In this study, geopolymer mortars made from blast furnace slag and steel slag reinforced by basalt fibre and polyvinyl alcohol (PVA) fibre were prepared to explore the effect on their strength and shrinkage properties. Scanning electron microscopy (SEM) was employed to characterize the reaction mechanism of the geopolymer mortars. The results show that both PVA fibre and basalt fibre can improve the mechanical properties of geopolymer mortars during the late curing period. The geopolymer reinforced by basalt fibre manifested a better toughness. A proper content of PVA fibres and basalt fibres can effectively reduce the drying and autogenous shrinkage of geopolymer mortars. The optimal content of basalt fibres and PVA fibres to reduce the drying shrinkage was 0.4%. The SEM results show that the fibres can effectively alleviate the stress concentration and prevent crack propagation.